Expand and simplify (3x+2) (x-5)

We expand this term by term.

To make sure we expand every term, I use the beak method. To do this, draw 2 curves over the equation from the 3x to the x, and then a second curve from the x to the +2.

Then draw 2 more curves, this time under the equation, from the 3x to the -5, and the second from the -5 to the +2.

You will notice the lines make an outline of a beak.

Now we are ready to multiply all of the lines.

3x * x = 3x2

x * 2 = 2x

3x * -5  = -15x

5 * 2 = -10

Now we simply add all of these calculated terms together:

3x2+2x-15x-10

We can do one step of simplification as there are two x terms:

2x-15x=-13x

This now gives us the final answer:

3x2-13x-10

Answered by Dominic S. Maths tutor

15303 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Solve the simultaneous equations 2x - y = 13, x - 2y = 11


What is the length of a if a triangle has lengths of b=6.4cm and c=5.6cm with an angle A=107.9 degrees?


A train travels for 240 minutes to travel a distance of 220 miles. Assuming the trains speed is constant, what is the train's speed in miles per hour?


Factorise fully 12x^2-20x+3


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2024

Terms & Conditions|Privacy Policy